Rancang Bangun Sistem Pengelolaan Kebersihan di Lingkungan Institut Teknologi Garut Berbasis Website - Ayu Latifah; Asri Mulyani; Tania Agusviani Wahidah (Jurnal Algoritma, 2022)
The utilization of information technology is quite influential on the human environment such as problems in the campus environment. The environment is a factor that influences human life. One of the problems faced in the campus environment is hygiene management. Reports on cleaning management that is still carried out conventionally make it difficult to monitor rooms or areas that have been cleaned because the reports provided may overlap with other data. Therefore, a management system is needed that is able to facilitate reporting on rooms or areas that have been cleaned and also monitoring carried out by related parties. The purpose of this research is to create a website-based cleaning management system in the campus environment. In order to make it easier for related parties to report cleanliness. The methodology applied in designing this system is the Rational Unified Process (RUP) through the stages of inception, elaboration, contraction, and transition. The modeling used when designing this system was the Unified Modeling Language (UML). The results of the research conducted produced an information system that can handle the management of environmental hygiene reports.